Microstructure and mechanical properties of sintered enamel hydroxyapatite - OKTAR, FAİK NÜZHET (ELSEVIER SCI LTD, 2007)
The influence of sintering temperature on the microstructure and the mechanical properties (i.e. compressive strength and microhardness) of samples of calcinated human enamel was investigated. The experimental results indicate a low densification regime after sintering at low temperatures (1000 degrees C, 1100 degrees C) and a high densification regime after sintering at higher temperatures (1200 degrees C, 1300 degrees C). With respect to earlier studies, high mechanical properties were achieved. The enhancement of mechanical properties was attributed to the presence of fluorine traces in enamel. (c) 2006 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: sintering; mechanical properties; hydroxyapatite; enamel; fluorine; BIOLOGICALLY DERIVED HYDROXYAPATITE; REINFORCED HYDROXYAPATITE; BIOCOMPATIBILITY EVALUATION; BOVINE HYDROXYAPATITE; DENTIN HYDROXYAPATITE; TOOTH-HYDROXYAPATITE; DRINKING-WATER; HIP FRACTURE; COATINGS; FLUORIDE